2012
DOI: 10.3354/meps09763
|View full text |Cite
|
Sign up to set email alerts
|

Offspring size and maternal environments mediate the early juvenile performance of two congeneric whelks

Abstract: Offspring size variation can have pervasive ecological and evolutionary implications for both offspring and mother, affecting an organism's performance throughout its life. Using 2 marine intertidal whelk species Cominella virgata and C. maculosa as model organisms, we examined how different maternal environments and contrasting hatchling size influence juvenile performance. The average size of field-collected hatchlings greatly differed between the species and at different scales of variation (i.e. among site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…A recent study of differently sized juveniles of C. virgata and C. maculosa kept in laboratory conditions also showed similar within‐ and between‐species differences in performance, with larger hatchlings of both species being, in most cases, less vulnerable to the stressors evaluated (desiccation and starvation) compared with smaller hatchlings (Carrasco et al. ). Together, these findings suggest that inter‐ and intraspecific differences in per‐offspring investment will not only mediate the performance of these juvenile whelks when faced with predators (as shown here), but will also affect growth rates and survival under different physical stressors.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A recent study of differently sized juveniles of C. virgata and C. maculosa kept in laboratory conditions also showed similar within‐ and between‐species differences in performance, with larger hatchlings of both species being, in most cases, less vulnerable to the stressors evaluated (desiccation and starvation) compared with smaller hatchlings (Carrasco et al. ). Together, these findings suggest that inter‐ and intraspecific differences in per‐offspring investment will not only mediate the performance of these juvenile whelks when faced with predators (as shown here), but will also affect growth rates and survival under different physical stressors.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies on juvenile performance for both species showed that growth rates of C. maculosa (~0.02 mm d −1 ) were nearly half those of C. virgata (~0.04 mm d −1 ) during the first month after hatching in laboratory conditions (Carrasco et al. ), and therefore, it is not surprising that juveniles of C. maculosa might require at least two more months to eventually reach the size refuge of ~4.8 mm SL and ~0.11 mm shell thickness observed in the less vulnerable 2‐month‐old juveniles of C. virgata .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful long‐distance dispersal might appear unlikely in Cominella because, similar to most buccinid whelks, all Cominella species whose development has been studied have been shown to undergo direct development (Anderson, ; Pilkington, ; van der Sman, Phillips & Pfister, ; Carrasco et al ., ) and their natural habitats do not usually include rafting materials. We note, however, that Bouchet & Warén () recorded buccinid egg capsules on pumice and Morley () has observed C. glandiformis egg capsules on both driftwood and oyster ( Saccostrea cucullata ) clumps.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 20 Cominella species are recognized, all of which are endemic to one of New Zealand (13 species), Norfolk Island (one species) or mainland Australia and Tasmania (six species) (Wilson ; Spencer et al ., ). This reciprocal species‐level endemism is in keeping with the high level of endemism (85%) typically observed among New Zealand molluscs (Spencer et al ., ) and reflects both the long period that New Zealand has been isolated from other land masses and the whelks' limited dispersal ability, a result of direct development (Anderson, ; Carrasco, Phillips & Perez‐Matus, ), as well as a low potential for rafting (see below).…”
Section: Introductionmentioning
confidence: 99%